Nanofabrication strategies for advanced electrode materials - Chen, Kunfeng; Xue, Dongfeng (Nanofabrication, 2017)
The development of advanced electrode materials for high-performance energy storage devices becomes more and more important for growing demand of portable electronics and electrical vehicles. To speed up this process, rapid screening of exceptional materials among various morphologies, structures and sizes of materials is urgently needed. Benefitting from the advance of nanotechnology, tremendous efforts have been devoted to the development of various nanofabrication strategies for advanced electrode materials. This review focuses on the analysis of novel nanofabrication strategies and progress in the field of fast screening advanced electrode materials. The basic design principles for chemical reaction, crystallization, electrochemical reaction to control the composition and nanostructure of final electrodes are reviewed. Novel fast nanofabrication strategies, such as burning, electrochemical exfoliation, and their basic principles are also summarized. More importantly, colloid system served as one up-front design can skip over the materials synthesis, accelerating the screening rate of high-performance electrode. This work encourages us to create innovative design ideas for rapid screening high-active electrode materials for applications in energy-related fields and beyond.